The Endocrine Milieu and CD4 T-Lymphocyte Polarization during Pregnancy - Polese, Barbara; Gridelet, Virginie; Araklioti, Eleni; Martens, Henri; Perrier d’Hauterive, Sophie; Geenen, Vincent (Frontiers in Endocrinology, 2014)
Acceptance of the fetal semi-allograft by the mother’s immune system has become the focus of intensive research. CD4+ T cells are important actors in the establishment of pregnancy. Th1/Th2 paradigm has been expanded to include CD4+ regulatory T (Treg) and Th17 cells. Pregnancy hormones exert very significant modulatory properties on the maternal immune system. In this review, we describe mechanisms by which the endocrine milieu modulates CD4 T-cell polarisation during pregnancy. We first focused on Treg and Th17 cells and on their importance for pregnancy. Secondly, we review the effects of pregnancy hormones (progesterone, estradiol) on immune cells previously described, with a particular attention to human chorionic gonadotropin (hCG). The importance of Treg cells for pregnancy is evidenced. They are recruited before implantation and are essential for pregnancy maintenance. Decreased number or less efficient Treg cells are implicated in fertility disorders. As for Th17 cells, the few available studies suggest that they have a negative impact on fertility. Th17 frequency is increased in infertile patients. With the combination of its pro-effects on Th2 and Treg cells and anti-effects on Th1 and Th17 cells, P4 contributes to establishment of a favorable environment for pregnancy. E2 effects are more dependent on the context but it seems that E2 promotes Treg and Th2 cells while it inhibits Th1 cells. hCG positively influences activities of Treg and uNK cells. This embryo signal is an essential actor for the success of pregnancy, both as the endocrine factor regulating P4 secretion by the ovarian corpus luteum, but also as a paracrine agent during implantation as well as an angiogenic and immunologic mediator during the course of gestation. LH immune properties begin to be studied but its positive impact on Treg cells suggests that LH could be a considerable immunomodulator in the mouse.